OTX2 regulates CFTR expression during endoderm differentiation and occupies 3′ cis‐regulatory elements. Issue 5 (26th January 2021) - Kerschner, Jenny L.; Paranjapye, Alekh; NandyMazumdar, Monali; Yin, Shiyi; Leir, Shih‐Hsing; Harris, Ann
Abstract: Background: Cell‐specific and developmental mechanisms contribute to expression of the cystic fibrosis transmembrane conductance regulator ( CFTR ) gene; however, its developmental regulation is poorly understood. Here we use human induced pluripotent stem cells differentiated into pseudostratified airway epithelial cells to study these mechanisms. Results: Changes in gene expression and open chromatin profiles were investigated by RNA‐seq and ATAC‐seq, and revealed that alterations in CFTR expression are associated with differences in stage‐specific open chromatin. Additionally, two novel open chromatin regions, at +19.6 kb and +22.6 kb 3′ to the CFTR translational stop signal, were observed in definitive endoderm (DE) cells, prior to an increase in CFTR expression in anterior foregut endoderm (AFE) cells. Chromatin studies in DE and AFE cells revealed enrichment of active enhancer marks and occupancy of OTX2 at these sites in DE cells. Loss of OTX2 in DE cells alters histone modifications across the CFTR locus and results in a 2.5‐fold to 5‐fold increase in CFTR expression. However, deletion of the +22.6 kb site alone does not affect CFTR expression in DE or AFE cells. Conclusions: These results suggest that a network of interacting cis ‐regulatory elements recruit OTX2 to the locus to impact CFTR expression during early endoderm differentiation. Key Findings: Two novel cis‐regulatory elements (CREs) were identified 3′ to the CFTR gene in an iPSC model of airway epithelial differentiation. These CREs appear transiently in definitive endoderm cells and are lost prior to activation of CFTR expression in anterior foregut endoderm cells. OTX2 occupies the CREs and regulates CFTR expression, through direct and/or indirect mechanisms Loss of OTX2 alters the local chromatin structure and activates CFTR transcription.